FEATURES of ORGANIZATION INDEPENDENT WORK DURING CLASSES OF PHYSICAL EDUCATION WITH STUDENTS-PHYSICIANS - Gubka, P.I. (World of Medicine and Biology, 2014)
The value of independent work is in-process investigation, as the component part of education, health and education of students-physicians. It was set that poor organized independent work, negatively influences on the health of students. Facilities and methods of independent physical preparation, that positively influence on the state of health and education of students, are certain.
Keywords: control; evaluation; student; independent work; complex of exercises